Estudio de vigilancia tecnológica en el cultivo de cacao - Cayetano Terrel, Paolo; Peña Pineda, Karla Mónica; Olivarez Rivera, Evelyn Lissete; Vargas Cisneros, Sandra Marilia (Instituto Nacional de Innovación Agraria, 2021)
64 páginas